PENGUATAN KELEMBAGAAN PEMERINTAHAN DESA MELALUI PEMBENTUKAN, PENGGABUNGAN DAN PENGHAPUSAN DESA - Rauf, Rahyunir (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2015)
In the effort applying of autonomous concept of countryside, is hence needed by a existence strive reinforcement to countryside governance, strength of it governance of countryside relied on by a serious consideration to two element which substansial, namely; ( 1) countryside as a(n) subsistem governance; and ( 2) countryside as social subsistem". Therefore, question of course; whether/what local government of regency able to and also local government of provinsi to can place its[his] best people to be assigned to assist in a[n process of management of governance in countryside storey;level, as well as have nothing like the doubt to give or overflow various form of kewenangan to element of countryside governance, this matter perhaps on condition that as long as can be followed with existence of clearer administrative technical guide, like who'll do what, and in his/its execution of bertanggungjawab whom. management of Governance of countryside in Indonesia pursuant to to state s philosophy of Five Principles and Constitution of Republic Of Indonesia of Year 1945, is such as those which arranged in section 2 Code/Law of Number 6 Year 2014 About Countryside, expressing that; " Management of Countryside Governance, Execution of Countryside Development, construction of Countryside social, and enableness of an society of countryside of pursuant to Five Principles, UUD of State of Republic Of Indonesia of Year 1945, Totalitarian State Republic Of Indonesia, and values of Bhineka Tunggal Ika". With dynamics needed by existence of Settlement of Countryside in the form of forming, affiliation and abolition of countryside to strengthen institute of countryside governance